Estudo clínico-patológico das distrofias estromais da córnea - Abreu, Elvira Barbosa [UNIFESP] (2016)
Introduction: Corneal dystrophy (CD) is defined as bilateral and symmetric primary corneal disease, without previous associated ocular inflammation. Corneal dystrophies (CDs) are classified according to the involved corneal layer in superficial, stromal, and posterior dystrophy. Incidence of each dystrophy varies according to the geographic region studied. Purpose: To evaluate the prevalence of stromal CDs among corneal buttons specimens obtained by penetrating keratoplasty (PK) in an ocular pathology laboratory and to correlate the diagnosis with patient age and gender. Methods: Corneal button cases of PK from January-1996 to May-2009 were retrieved from the archives of The Henry C. Witelson Ophthalmic Pathology Laboratory and Registry, Montreal, Canada. The cases with histopathological diagnosis of stromal CDs were stained with special stains (Peroxid Acid Schiff, Masson Trichrome, Congo Red and Alcian Blue) (analyzed under polarized light) for classification and correlated with epidemiological information (age at time of PK and gender) from patient?s file. Results: A thousand and three hundred consecutive corneal buttons cases were retrieved. Stromal CD was found in 40 (3,1%) cases. Lattice CD was the most prevalent with 26 cases (65%). Nineteen were female (73.07%) and the PK was performed at average age of 59,3 years old. Combined CD was found in 8 (20%) cases, 5 (62.5%) of them were female and the average age of the PK was 54.8 years old. Granular CD was represented by 5 (12,5%) cases, and 2 (40%) of them were female. PK was performed at average age of 39,5 years old. Macular CD was present in only one (2,5%) case, in a 36 years old female. Conclusion: Systematic histopathological approach and evaluation, including special stains in all stromal corneal dystrophies, is critical to establish the correct diagnosis.